Etiology and Outcome of Ischemic Stroke in Patients With Renal Impairment Including Chronic Kidney Disease: Japan Stroke Data Bank. (26th April 2022) - Miwa, Kaori; Koga, Masatoshi; Nakai, Michikazu; Yoshimura, Sohei; Sasahara, Yusuke; Koge, Junpei; Sonoda, Kazutaka; Ishigami, Akiko; Iwanaga, Yoshitaka; Miyamoto, Yoshihiro; Kobayashi, Shotai; Minematsu, Kazuo; et al.
Abstract : Background and Objectives: Chronic kidney disease is a worldwide public health problem that is recognized as an established risk factor for stroke. It remains unclear whether its distribution and clinical impact are consistent across ischemic stroke subtypes in patients with renal impairment. We examined whether renal impairment was associated with the proportion of each stroke subtype vs ischemic stroke overall and with functional outcomes after each stroke subtype. Methods: Study participants were 10, 392 adult patients with an acute stroke from the register of the Japan Stroke Data Bank, a hospital-based multicenter stroke registration database, between October 2016 and December 2019, whose baseline serum creatinine levels or a dipstick proteinuria result were available. All ischemic strokes were classified according to the Trial of Org 10172 in Acute Stroke Treatment criteria. Unfavorable functional outcome was defined as modified Rankin Scale (mRS) score 3–6 at discharge. Mixed effect logistic regression was used to determine the relationship between the outcomes and the estimated glomerular filtration rate (eGFR), eGFR strata (<45, 45–59, ≥60 mL/min/1.73 m 2 ), or dipstick proteinuria ≥1 adjusted for covariates. Results: Overall, 2, 419 (23%) patients had eGFR 45–59 mL/min/1.73 m 2 and 1, 976 (19%) had eGFR <45 mL/min/1.73 m 2, including 185 patients (1.8%) receiving hemodialysis. Both eGFR 45–59 and eGFR <45 mL/min/1.73 m 2 were associated with a higher proportion of cardioembolic stroke (odds ratio [OR], 1.21 [95% CI, 1.05–1.39] and 1.55 [1.34–1.79], respectively) and a lower proportion of small vessel occlusion (0.79 [0.69–0.90] and 0.68 [0.59–0.79], respectively). A similar association with the proportion of these 2 subtypes was proven in the analyses using decreased eGFR as continuous values. Both eGFR <45 mL/min/1.73 m 2 and proteinuria were associated with unfavorable functional outcomes in patients with cardioembolic stroke (OR, 1.30 [95% CI, 1.01–1.69] and 3.18 [2.03–4.98], respectively) and small vessel occlusion (OR, 1.44 [1.01–2.07] and 2.08 [1.08–3.98], respectively). Discussion: Renal impairment contributes to the different distributions and clinical effects across specific stroke subtypes, particularly evident in cardioembolic stroke and small vessel occlusion. This possibly indicates shared mechanisms of susceptibility and potentially enhancing pathways.